MICROENCAPSULATION OF PROBIOTICS BY USING EXTERNAL IONIC GELLING PECTIN - Menezes, Maria Fernandada Silveira Cáceres de (2015)
The increase in global life expectancy has aroused the interest of consumers for healthy food, driving the development of functional foods containing probiotics, of which stand out genera, Lactobacillus spp, Bifidobacterium spp and Enterococcus spp, known to carry beneficial effects in the colon. Various microencapsulation techniques and coating materials have been explored, the external ionic gelation has proved to be viable preservation of the probiotics cultures. Natural polymers have been studied, such as pectin, raw material can be obtained from the citrus industry waste extraction. Pectins are classified according to their degree of methoxylation, which influences its hydration capacity and gel formation. As a dietary fiber, pectin acts as a substrate for the microflora of the colon, stimulating it. For these characteristics, the use of pectin as a coating material microparticles probiotic is presented as an alternative for carrying out works aimed to study the production, characterization, and Microparticles feasibility of in vitro cultures. This review aims to present microencapsulation of probiotics through external ionic gelation method, as well as address the microcapsules coating materials, with emphasis on the use of pectin.